2018
DOI: 10.3390/rs10020283
|View full text |Cite
|
Sign up to set email alerts
|

SBAS Analysis of Induced Ground Surface Deformation from Wastewater Injection in East Central Oklahoma, USA

Abstract: The state of Oklahoma has experienced a dramatic increase in the amount of measurable seismic activities over the last decade. The needs of a petroleum-driven world have led to increased production utilizing various technologies to reach energy reserves locked in tight formations and stimulate end-of-life wells, creating significant amounts of undesirable wastewater ultimately injected underground for disposal. Using Phased Array L-band Synthetic Aperture Radar (PALSAR) data, we performed a differential Synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Qiao et al [15] show a strong correlation between changes in terrain height and gas pressure in the UGS. Loesch and Vasit [16] deal with the impact of oil and gas extraction and the simultaneous injection of wastewater on the seismicity of the area. They show, inter alia, that areas showing vertical movements can be bounded by tectonic faults.…”
Section: Introductionmentioning
confidence: 99%
“…Qiao et al [15] show a strong correlation between changes in terrain height and gas pressure in the UGS. Loesch and Vasit [16] deal with the impact of oil and gas extraction and the simultaneous injection of wastewater on the seismicity of the area. They show, inter alia, that areas showing vertical movements can be bounded by tectonic faults.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these advantages and characteristics, InSAR technology has been successfully applied to the monitoring of volcanic motion [8,9], seismic activity [10,11], landslides [12,13], glacial drift [14,15], regional ground sink [16,17], and anthropogenic activity like tunneling or infrastructure monitoring [18][19][20]. In addition, InSAR technology has also been successfully used to monitor ground deformation over oil and geothermal fields, such as the Helliishdi geothermal field [21], the West Texas oilfield [22], and the Cushing oilfield in East Central Oklahoma [23].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, monitoring recent surface deformations over the Karamay oilfield area is of great significance for guiding the continued exploitation for oil and gas. Liquid injection may cause local stress changes, which can lead to earthquakes [21,23,27]. Are the low-magnitude earthquakes within and around the oilfield related to oil and gas exploration in this area?…”
Section: Introductionmentioning
confidence: 99%
“…subsidence was reported to coincide with a zone of densely located injection wells in Oklahoma (Loesch & Sagan, 2018). However, more localized studies in parts of Texas and Oklahoma have shown uplift in areas of injection (Barba-Sevilla et al, 2018;Shirzaei et al, 2016;Zheng et al, 2019).…”
Section: G6mentioning
confidence: 99%